Expression of secretory calcium-binding phosphoprotein (scpp) genes in medaka during the formation and replacement of pharyngeal teeth - Tsuyoshi Morita; Shin Matsumoto; Otto Baba (BMC, 2023)
Abstract Background Analyses of tooth families and tooth-forming units in medaka with regard to tooth replacement cycles and the localization of odontogenic stem cell niches in the pharyngeal dentition clearly indicate that continuous tooth replacement is maintained. The secretory calcium-binding phosphoprotein (scpp) gene cluster is involved in the formation of mineralized tissues, such as dental and bone tissues, and the genes encoding multiple SCPPs are conserved in fish, amphibians, reptiles, and mammals. In the present study, we examined the expression patterns of several scpp genes in the pharyngeal teeth of medaka to elucidate their roles during tooth formation and replacement. Methods Himedaka (Japanese medaka, Oryzias latipes) of both sexes (body length: 28 to 33 mm) were used in this study. Real-time quantitative reverse transcription-polymerase chain reaction (PCR) (qPCR) data were evaluated using one-way analysis of variance for multi-group comparisons, and the significance of differences was determined by Tukey's comparison test. The expression of scpp genes was examined using in situ hybridization (ISH) with a digoxigenin-labeled, single-stranded antisense probe. Results qPCR results showed that several scpp genes were strongly expressed in pharyngeal tissues. ISH analysis revealed specific expression of scpp1, scpp5, and sparc in tooth germ, and scpp5 was continually expressed in the odontoblasts of teeth attached to pedicles, but not in the osteoblasts of pedicles. In addition, many scpp genes were expressed in inner dental epithelium (ide), but not in odontoblasts, and scpp2 consistently showed epithelial-specific expression in the functional teeth. Taken together, these data indicate that specific expression of scpp2 and scpp5 may play a critical role in pharyngeal tooth formation in medaka. Conclusion We characterized changes in the expression patterns of scpp genes in medaka during the formation and replacement of pharyngeal teeth.